A Merit-based Scholarship Assessment System a Case Study of Uganda Christian University Bishop Barham University College- Kabale - Trust Ahumuza (Uganda Christian University, 2025)
This research project focused on the development of a Merit-Based Scholarship Assessment System for Uganda Christian University, Bishop Barham University College. The study aimed to investigate the challenges faced in the current manual scholarship application processes, assess the level of satisfaction among students and administrators, and propose a digital solution to improve fairness, efficiency, and transparency. A combination of methods was employed, incorporating the distribution of about 274 questionnaires, of which 218 were successfully returned and analyzed. The findings revealed that the manual system was slow, confusing, and lacked clear communication and transparency. Many students reported difficulties in submitting documents, tracking their application status, and understanding eligibility criteria. Satisfaction levels with the current system were generally low. Based on the findings, an online scholarship management system was proposed, featuring online applications, document uploads, real-time status updates, an online helpdesk, and automated assessment based on predefined merit criteria. The study concluded that introducing a web-based platform would greatly enhance the scholarship application experience, improve transparency in award decisions, and reduce administrative workload. The project recommends that Uganda Christian University prioritize the development and implementation of such a system to better serve students and foster trust in the scholarship allocation process.